Making sense of recovery after traumatic brain injury through a peer mentoring intervention: a qualitative exploration. Issue 10 (10th October 2018) - Kersten, Paula; Cummins, Christine; Kayes, Nicola; Babbage, Duncan; Elder, Hinemoa; Foster, Allison; Weatherall, Mark; Siegert, Richard John; Smith, Greta; McPherson, Kathryn
Abstract : Objective: To explore the acceptability of peer mentoring for people with a traumatic brain injury (TBI) in New Zealand. Design: This is a qualitative descriptive study exploring the experiences reported by mentees and mentors taking part in a feasibility study of peer mentoring. Interviews with five mentees and six mentors were carried out. Data were analysed using conventional content analysis. Setting: The first mentoring session took place predischarge from the rehabilitation unit. The remaining five sessions took place in mentees' homes or community as preferred. Participants: Twelve people with TBI took part: six mentees (with moderate to severe TBI; aged 18–46) paired with six mentors (moderate to severe TBI >12 months previously; aged 21–59). Pairing occurred before mentee discharge from postacute inpatient brain injury rehabilitation. Mentors had been discharged from rehabilitation following a TBI between 1 and 5 years previously. Intervention: The peer mentoring programme consisted of up to six face-to-face sessions between a mentee and a mentor over a 6-month period. The sessions focused on building rapport, exploring hopes for and supporting participation after discharge through further meetings and supported community activities. Results: Data were synthesised into one overarching theme: making sense of recovery. This occurred through the sharing of experiences and stories; was pivotal to the mentoring relationship; and appeared to benefit both mentees and mentors. Mentors were perceived as valued experts because of their personal experience of injury and recovery, and could provide support in ways that were different from that provided by clinicians or family members. Mentors required support to manage the uncertainties inherent in the role. Conclusions: The insight mentors developed through their own lived experience established them as a trusted and credible source of hope and support for people re-engaging in the community post-TBI. These findings indicate the potential for mentoring to result in positive outcomes.